Sistem, Pendukung Sistem Pendukung Keputusan Pemilihan Smartphone Gaming Android Terbaik Dengan Metode Weighted Product - Syifa Nur Rakhmah -; Raden Aldhi Rajendra Yusuf (LPPM Universitas Bina Sarana Informatika, 2022)
The lack of information in choosing an effective android gaming smartphone makes it difficult for people to choose the best gaming smartphone while people only know about ordinary smartphones with criteria that are not for games. By conducting this research, it can provide information in making decisions to determine the best Android gaming smartphone. Solutions using a decision support system using the Weighted Product (WP) method, the Weighted Product method can assist in making decisions but calculations using this method only produce the largest value that will be selected as the best alternative. The targeted population is the area of North Bekasi which amounted to 329,976 people with a presentation of leeway of five percent (5%) using the slovin formula and the results obtained were 399.515 rounded up to 400 samples. The criteria that have been set based on standard specification data for gaming smartphones for playing games are (price, battery, RAM, ROM, Chipset, and GPU) as well as alternatives selected based on the best gaming cellphones in 2021, namely Asus ROG Phone 3, Black Shark 3, Realme X50 Pro 5G, OPPO Find X2 Pro, Nubia Red Magic 5G. By using a decision support system using the Weighted Product method, it is concluded that the selection of the best Smartphone Gaming at this time in the North Bekasi area and the appropriate criteria have obtained satisfactory results in the selection of the best Gaming Smartphone. In other words, Asus ROG Phone 3, Black Shark 3 and OPPO Find X2 Pro are recommended as the best Android Gaming Smartphones today.